Py-GC/MS as a complementary technique for the chemical characterization of small microplastics (<100 μm) in polar samples - Gregoris, Elena (Zenodo, 2021)
Introduction Microplastics are a class of emerging pollutants of great concern, since they are widely distributed in the environment and biota, and have also been found in polar regions (Iannilli et al., 2019). Currently there are no standard methods for the identification and quantification of microplastics in environmental samples. Micro-FTIR is a nondestructive spectroscopic technique, that allows polymer identification and quantification in abundance and weight (Corami et al. 2020 and 2021); thanks to the instrument's imaging, particle morphology and size can be evaluated. Mass-based analytical methods – like pyrolysis gas chromatography-mass spectrometry (Pyr-GC/MS) - lack the information on particle size and morphology, but they are time efficient and permit a successful identification of polymer types and quantification of plastic weight (Müller et al., 2020). The cross-validation among techniques allows the standardization of pretreatment and analytical methods. In this abstract, we describe the state of the art of our work, whose aim is a cross-validation of two different techniques: quantification (i.e., abundance and weight) and simultaneous identification of microplastic particles (MPs) and small MPs (SMPs) using Micro-FTIR, and identification and quantification of MPs and SMPs using Pyr-GC/MS. These techniques will be employed for the analysis of polar samples. Activities The first phase of the work was dedicated to recognizing the characteristic pyrolysis products necessary to identify some standard polymers plastic materials. Preliminary results were obtained from different environmental matrices. Few water samples from Venice Lagoon and few permafrost samples collected in Svalbard Islands were analyzed via Micro-FTIR and Pyr/GC-MS. The identification of the single peaks in chromatograms was carried out using the NIST 05 library and based on the information available in the literature. The presence of PE was confirmed in all the samples with both techniques. Our data suggest that Pyr-GC/MS could be successfully used for the identification and quantification of MPs, combined with Micro-FTIR. Future developments We are going to create a comprehensive library of characteristic pyrolysis products, to increase the chance of recognising plastic materials in polar samples. In addition, the use of Pyr-GC/MS allows the recognition of smaller molecules used as additives in plastics, that can be released in environment and create a serious threat. This work could help in reporting the occurrence of emerging contaminants in polar regions, but could also give an additional point of view in other topics, such as contaminant transport to the Poles, the ecosystem response to contaminants exposure, the interaction between various environmental domains. References Corami F., Rosso B., Roman M., Picone M., Gambaro A., and Barbante C.; Evidence of small microplastics (<100 μm) ingestion by Pacific oysters (Crassostrea gigas): A novel method of extraction, purification, and analysis using Micro-FTIR. Marine Pollution Bulletin, 160, 111606, doi: 10.1016/j.marpolbul.2020.111606, 2020 Corami F., Rosso B., Morabito E., Rensi V., Gambaro A., and Barbante C,; Small microplastics (<100 μm), plasticizers and additives in seawater and sediments: Oleoextraction, purification, quantification, and polymer characterization using Micro-FTIR. Science of The Total Environment, 797, 148937, doi: 10.1016/j.scitotenv.2021.148937, 2021. Iannilli V., Pasquali V., Setini A., and Corami F.; First evidence of microplastics ingestion in benthic amphipods from Svalbard. Environmental Research, 179, Part A, 108811, doi: 10.1016/j.envres.2019.108811, 2019. Müller, Y.K., Wernicke, T., Pittroff, M., Witzig, C.S., Storck, F.R., Klinger, J., and Zumbülte, N.:Microplastic analysis—are we measuring the same? Results on the first global comparative study for microplastic analysis in a water sample, Analitical and Bioanalitical Chemistry, 412, 555–560, doi: 10.1007/s00216-019-02311-1, 2020.